Clientelismo, patronazgo y corrupción en Colombia y México - González Tule, Luis Antonio (Colección Gobierno local., 2019)
More than two decades ago, the prominent Argentine political scientist Guillermo Odonnell raised the need to get rid of the excessive "fixation on complex and highly formalized organizations" to understand the functioning of democracies under new institutional designs. This book responds to the need to investigate the real functioning of Latin American democracies, analyzing the informal rules of political exchange and distribution of resources in Colombia and Mexico. It is intended to know how politicians and parties co-opt votes beyond activities.